A case report of ethanol infusion in the vein of Marshall using the right jugular vein approach. Issue 5 (26th August 2020) - Philibert, Severine; Amet, Denis; De Chirac, Margaux; Laurent, Gabriel
Abstract: Background: Ethanol infusion has recently been described as a curative strategy for certain peri-mitral flutters by blocking electrical conduction across the mitral isthmus along with the Marshall bundle. The present case showed that a right jugular vein approach, less described, may be a good choice when performing an ethanol infusion in the vein of Marshall (VOM). Case summary: A 45-year-old man was admitted to our unit for dyspnoea associated with an atypical atrial flutter with a cycle length of 320 ms. The left atrial activation map showed a peri-mitral counter-clockwise circuit. The atrial flutter cycle length went up to 345 ms once an endocardial and epicardial point-by point-ablation of the mitral line was completed. At this stage, a new activation map showed that the mitral line was still permeable with an epicardial conduction bridge through the VOM. We decided to use an ethanol infusion for the ablation of the VOM. The coronary sinus could not be thoroughly catheterized due to a winding and angular shape so we decided to try a right jugular vein approach. A total of 9 mL of ethanol was injected into the VOM. A final venogram showed the diffusion of ethanol around the VOM. Sinus rhythm was restored during the last ethanol infusion. A new voltage map confirmed the completion of the mitral line, and we confirmed the bidirectional block. Discussion: The present case showed that a right jugular vein approach may be a good choice when catheterizing and performing an ethanol infusion in the VOM.